A Case of Cholangitis Glandularis Proliferans and Cholangiocarcinoma of the Common Bile Duct. Issue 3 (1993) - Richardson, A. J.; Grierson, J. M.; Tait, N.; Williams, S. J.; Little, J. M.
Abstract : A case of Cholangitis Glandularis Proliferans (CAGP) in association with a cholangiocarcinoma of the common bile duct as described. This is the eighth case of CAGP described and the second association with cholangiocarcinoma.